An evaluation of Thais’ attitude toward Telepharmacy in community pharmacies: A cross-sectional survey study - Maneemai, Ongart; Jaroenpiyapat, Patchalee; Wongwiwattana, Pimlapus; Phatthanasobhon, Sirayut (Edelweiss Applied Science and Technology, 2024)
To determine the Thais’ attitudes toward telepharmacy in community pharmacies service and explore the factor effected their attitudes. This cross-sectional survey study conducted in Thailand. The population was Thai citizens over the age of 18 years. Data was gathering via online questionnaire. Descriptive statistics were examined. Subgroup analysis was evaluated by t-test or one way ANOVA as appropriate. The factors affecting Thais’ attitudes regarding telepharmacy were tested with multiple regression analysis. Total of 391 respondents were analyzed. Overall mean score of attitudes on telepharmacy was 4.15  0.45. The highest rating was given to telepharmacy procedures (4.49  0.49). Females had higher opinion mean scores than males (4.18  0.44 vs. 4.08  0.48; p = 0.017) and healthcare people performed poorly opinions mean scores than the general population (4.09  0.44 vs. 4.19  0.47, p = 0.026). The factors that influenced the opinion score were gender (p = 0.017), income (p = 0.036), and working or studying in the medical field (p = 0.011). Telepharmacy is a crucial service offered by community pharmacies. It facilitated clients’ access to medications and pharmacists. Gender, income, and working or studies in the medical area influenced the Thais’ opinion.